Burner tilting angle effect on velocity profile in 700 MW utility boiler - Munisamy K.M.; Yusoff M.Z.; Thangaraju S.K.; Hassan H.; Ahmad A. (Institute of Physics Publishing, 2023)
Boiler firing; Boilers; Pulverized fuel fired boilers; Boiler operators; Design condition; Fire ball; Firing angle; Off designs; Tilting angle; Utility boiler; Velocity profiles; Coal fired boilers